Procedural Law of Medieval Church (ordo iudiciarius) in the Context of the Defendant’s Right to Due Process - Lukošius, Tadas (Teisė, 2023)
The paper examines the development of the Church’s procedural law ordo iudiciarius in the period from the middle of the 12th century to the end of 13th century. By looking from the perspective of the defendant’s right to a due process, the author aims to reveal circumstances for the formation of ordo iudiciarius and its main features in the stages when the opposing procedure models (accusatorial and inquisitorial) were applied in the Church courts.
Keywords: ordo iudiciarius; Church’s procedural law; Canon Law; Roman Law